ELORM-DONKOR, Lord and Clifton CLARKE. African Pentecostal Missions Maturing: Essays in Honor of Apostle Opoku Onyinah. (17th April 2019) - Amamnsunu, Johnson
Abstract : ELORM-DONKOR, Lord and Clifton CLARKE. African Pentecostal Missions Maturing: Essays in Honor of Apostle Opoku Onyinah. Eugene, OR: Wipf and Stock, 2018. 306pp. Pbk. ISBN: 9781532618352. 36.00.